TYPE 2 DIABETES MELLITUS: PATHOPHYSIOLOGY, DIAGNOSTICS, AND CONTEMPORARY THERAPEUTIC STRATEGIES. A REVIEW - Wiater, Dominik; Szkodziński, Kacper; Jakubczyk, Inga; Maternia, Jagoda; Łoś, Aleksandra; Majowicz-Czaszyńska, Karolina; Pempuś, Wiktoria; Król, Nikola; Tomaszek, Barbara; Blok, Aleksandra; Płodzień, Gabriela (International Journal of Innovative Technologies in Social Science, 2026)
Type 2 diabetes mellitus (T2DM) remains one of the dominant clinical challenges in modern medicine. According to the 11th edition of the IDF Diabetes Atlas (2025), 589 million adults currently suffer from this condition, and it is estimated that by 2050, the number of patients will increase by 46%, reaching 853 million.This paper reviews current knowledge on the pathogenesis of T2DM, which includes peripheral insulin resistance, the progressive loss of pancreatic beta-cell mass alongside secondary impairment of their secretory function, and systemic inflammation. Diagnostic criteria are presented in accordance with the 2025 PTD (Diabetes Poland) guidelines, including recommendations for screening and the identification of high-risk groups.A fundamental part of the study is devoted to modern pharmacotherapy, with a particular focus on SGLT-2 inhibitors and GLP-1 receptor agonists as drugs with documented cardioneproprotective effects. Furthermore, the role of metabolic surgery and the importance of comprehensive, multidisciplinary care in the prevention and treatment of organ-related complications are discussed.